Sodium-glucose cotransporter-2 inhibitor therapy improves renal and hepatic function in patients with cirrhosis secondary to metabolic dysfunction associated steatotic liver disease and type 2 diabetes - Colletta, Alessandro; Cooper, Katherine M.; Placentino, Giuseppe; Devuni, Deepika; Colletta, Cosimo (Frontiers in Endocrinology, 2025)
PurposeMetabolic dysfunction-associated steatotic liver disease (MASLD) increases the risk of chronic kidney disease (CKD), compounding morbidity in patients with cirrhosis. Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are disease-modifying agents in type 2 diabetes mellitus (T2DM) and CKD, but studies on their use in cirrhosis are limited. We aimed to assess the effect of SGLT2i therapy on renal and hepatic function in patients with Child-Turcotte-Pugh (CTP) B cirrhosis and T2DM.MethodsWe conducted a 48-month longitudinal, retrospective cohort study of 54 patients with CTP B cirrhosis secondary to MASLD and T2DM who were initiated on SGLT2i (n=27) or insulin (n=27). Laboratory data were collected every 3 months. Liver stiffness (LS) was measured every 6 months via transient elastography (TE) and acoustic radiation force impulse with shear wave velocity (ARFI-SWV). The primary outcome was change in glomerular filtration rate (GFR) and chronic kidney disease (CKD) stage. Secondary outcomes included LS changes measured via TE and ARFI. Additional end points included MELD-Na, MELD 3.0, CTP scores, hepatic decompensations, proteinuria, body mass index (BMI), hemoglobin A1c (Hb-A1c), blood glucose (BG).ResultsAt baseline, the two groups were comparable in GFR (SGLT2i: 55.6 ± 1.9 vs. insulin: 58.1 ± 2.1 mL/min/1.73 m², p = 0.37), CKD stage, ARFI-SWV (2.9 ± 0.1 vs. 2.8 ± 0.1 m/s, p = 0.26), MELD-Na, and MELD 3.0. The SGLT2i group was older (p < 0.01) and had higher AST (p=0.01), ALT (p<0.01), and CTP scores (p=0.02), but lower LS by TE (p = 0.03). Over 48 months, GFR increased in the SGLT2i group (+13.5 ± 1.3) and declined in the insulin group (−4.2 ± 1.4; p < 0.01). A greater proportion of SGLT2i patients transitioned from CKD stage 3a to 2 (p = 0.04). Liver stiffness by TE decreased in the SGLT2i group (−4.0 ± 1.1 kPa), while it increased in the insulin group (+3.0 ± 2.5 kPa; p < 0.01). ARFI-SWV also declined in the SGLT2i group but increased in the insulin group (2.5 ± 0.1 vs. 3.2 ± 0.1 m/s; p < 0.01). The SGLT2i group also demonstrated significant improvement in MELD-Na, MELD 3.0 and CTP scores, with greater resolution of hepatic decompensations, proteinuria, as well as better BMI and HbA1c outcomes (all p < 0.01).ConclusionsPatients with CTP B cirrhosis and T2DM receiving SGLT2i therapy experienced a significant improvement in renal, hepatic function, and glycemic control over 48 months compared to patients treated with insulin.